2003
DOI: 10.1007/s10350-004-6754-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Clinical Trial of Ligasure™ vs. Conventional Diathermy in Hemorrhoidectomy

Abstract: Ligasure diathermy provides a superior alternative to conventional diathermy in hemorrhoidectomy by reducing operating time and postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
70
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 15 publications
10
70
2
Order By: Relevance
“…However, we were not able to confirm these favorable results as reported in previous published studies [5,8,[15][16][17][18][19][20][21][22][23][24]. Most of these laparoscopic studies involved bowel surgery and compared LigaSure with ultrasonic devices [8,16,19,20].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, we were not able to confirm these favorable results as reported in previous published studies [5,8,[15][16][17][18][19][20][21][22][23][24]. Most of these laparoscopic studies involved bowel surgery and compared LigaSure with ultrasonic devices [8,16,19,20].…”
Section: Discussioncontrasting
confidence: 57%
“…The use of a feedback-controlled bipolar cutting device (vessel-sealing device) has been assessed for a range of procedures, including abdominal and vaginal hysterectomy, hemorrhoidectomy, and bowel surgery [4][5][6][7][8][9][10][11][12]. Several studies reported a decrease in operating time or operative blood loss using vessel-sealing devices in comparison to other hemostatic devices [5][6][7][8]12].…”
mentioning
confidence: 99%
“…However, a patient complained of prolonged pain for ten days after LigaSure ® hemorrhoidectomy. Franklin et al (8) reported that LigaSure ® hemorrhoidectomy reduces postoperative pain and the time to fi rst defecation. However, in the present study, the time of return of peristalsis was not different between the two groups Application of LigaSure ® for hemorrhoidectomy reduced operating time and operative blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Application of thermal vessel sealing systems has provided many advantages to surgical procedure such as reduced operation time, reduced peroperative blood loss and simplifi ed dissection (6,8,13). Less thermal injury results in less postoperative pain (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation